2020
DOI: 10.1002/ehf2.13046
|View full text |Cite
|
Sign up to set email alerts
|

Exploring correlates of improved depression symptoms and quality of life following tai chi exercise for patients with heart failure

Abstract: Aims Tai chi exercise has been shown in a prior randomized controlled trial to improve depression symptoms and quality of life (QoL) in patients with heart failure (HF), but correlates of these improvements are not well known. The purpose of this secondary analysis was to explore whether tai chi is associated with improvements in biopsychosocial and behavioural measures and whether such improvements are correlated with improved depression and QoL. Methods and results Participants were n = 100 adults with chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Among the reasons for difficulties with regular physical activity, lack of self‐confidence, avoiding physical activity in the winter to prevent illness (value of being healthy) and difficulties in establishing new habits (value of maintaining a healthy lifestyle) emerged. Studies show 34 that group exercise programmes have shown success in addressing these challenges, improving exercise self‐efficacy and supporting regular activity engagement of HF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among the reasons for difficulties with regular physical activity, lack of self‐confidence, avoiding physical activity in the winter to prevent illness (value of being healthy) and difficulties in establishing new habits (value of maintaining a healthy lifestyle) emerged. Studies show 34 that group exercise programmes have shown success in addressing these challenges, improving exercise self‐efficacy and supporting regular activity engagement of HF patients.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of that time, the changes in their anxiety subscale were significant (p = 0.002), as were the changes in their depression subscale (p = 0.008). Luberto et al [73] found that the practice of tai chi by patients with heart failure improved their depression symptoms and quality of life indexes. Lopez et al [74] found that group tai chi and qigong classes taken by cancer patients and caregivers experienced significant improvement in global distress.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the research areas are mainly concentrated in self-care, physical activity, outcomes, meta-analysis, etc. (14)(15)(16), and there is a lack of mechanism research and interdisciplinary cooperation. As a result, some important mechanisms in related fields cannot be applied in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Over the same period, the number of publications met the criteria "heart failure" AND "exercise" (Cohort 2) is 15 1B,E).…”
Section: Characteristic Analysis Of Related Publications (Number and Trends) In Timementioning
confidence: 99%
See 1 more Smart Citation